CATTLE CAN DEVELOP LUMPY DERMATITIS DEPENDING ON THE SEASON - Tursunov Sokhib Samariddinovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Information is provided on the seasonal occurrence of nodular dermatitis in cattle in 200 heads of the Taraqqiyot farm in Yangi Yul district of Tashkent region, in a total of 120 heads of cattle, including 85 dairy cows and 30 bulls, in the Boz-Suv Chorva va Parranda invest farm in the same district, in the Ergash Ota cattle farm in Yukorichirchik district of Tashkent region (1150 heads), in 75 heads of productive cattle in the Saraykul vetpunkt of Takhiatash district of the Republic of Karakalpakstan, and in 35 heads of cattle in the Toshpulotov Bahodir Juraniyozovich farm in Sherabod district of Surkhandarya region, in a total of 1580 cattle.